Reflections on Educational Work in the Area of Italian Mental Health - Gambacorti-Passerini, Maria Benedetta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper specifically reflects on educational work in the area of mental health, on the basis of an empirical research designed to explore the interaction between medical and pedagogical interventions in two Italian mental health contexts.The study design was qualitative (Denzin & Lincoln, 2000); specifically a phenomenological-hermeneutical method (Van Manen, 1990) and a case-study strategy (Nagy & Leavy, 2011; Yin, 1994) were adopted. An analysis of educational work in healthcare contexts was carried out, with a focus on the particular knowledge, professional role and professional practices that identify educators in this field.The case study pointed up critical and specific characteristics of educational action in the mental health services, which is aimed at striking a balance between the dimensions of caring for, and developing the skills of, people with mental illness.